A Literature Study of Marketing Strategies in Product Development Using Design Thinking Method - Ridho Muhammad; Laura Lahindah (International Journal of Economics (IJEC), 2023)
Objective study This is for reviewing marketing strategies in product development using the design thinking method. As for the method of study This is a qualitative study, and research qualitative is a research method used to understand social phenomena in depth. As for Types of research used by researchers, i.e. A literature study is carried out by researchers by collecting, studying, and analyzing references or sources obtained in written form, such as books, journals, articles, documents, and other sources of information that are significant to the topic or title being researched. And then the researcher analyzes and draws conclusions to find answers to what the researcher is studying. The results of the research show that a marketing strategy based on design thinking is a holistic approach that brings significant changes to the way companies approach product development and brand communication. By prioritizing a deep understanding of user needs, embracing creativity and innovation, and being responsive to consumer feedback, companies can achieve a competitive advantage and build strong relationships with consumers.